Osvrt na bibliografiju hrvatskih prijevoda iz poljske književnosti u 2014. godini / Komentarz do bibliografii przekładów literatury polskiej w Chorwacji w 2014 roku (tłum. Katarzyna Majdzik) - Rogić Musa, Tea (Przekłady Literatur Słowiańskich, 2015)
Review of Croatian translations of Polish literature published in the 2014 The paper deals with professional translations of Polish literature into Croatian language, published in Croatia in 2014, based on bibliographic access to translation issues. Concise and informative comments of each publication, its literary profile, its translator and publisher, as well as the summary, refer to the perception of Polish literature and the nature of cultural exchange that is achieved thanks to the translations. Key words: Polish literature; Croatian translations; Bibliography of translation 2014